ENHANCING ENGLISH FOR NETWORKING, PRESENTATION, AND COLLABORATION (ENPC) COMPETENCIES THROUGH AN INTERNATIONAL VISITING LECTURE: A DESCRIPTIVE REFLECTIVE CASE STUDY - Ela Kristi Permatasari; Dawit Dibekulu; Lutfiana Lutfiana; Zaky Dzulhiza Hawin Amalia; Estiningtyas Sholikhah; Ryan Fitrian Pahlevi (English Education Department at FKIP Nommensen University, 2026)
English language education in higher education increasingly emphasizes authentic and competency-based learning to prepare students for global academic and professional communication. Within this context, international visiting lectures are often positioned as part of internalization at home initiatives that provide intercultural exposure without physical mobility. This study aims to document and examine the implementation of an international visiting lecture entitled “Beyond the Classroom: English for Networking, Presentation, and Collaboration” and to explore how such an activity supports the development of English for Networking, Presentation, and Collaboration (ENPC) competencies among undergraduate English Education students at Universitas Muhammadiyah Brebes. Adopting a descriptive reflective case study design, qualitative data were collected from 47 participants through online survey responses, individual reflection logs, and selected student produced learning artifacts. The data were analyzed thematically and triangulated across sources to identify recurring patterns in participants’ experiences and perceived learning outcomes. The findings indicate that students reported increased awareness and confidence in using English for networking, presentation, and collaborative communication, alongside heightened intercultural awareness and learning motivation. Reflection narratives and learning artifacts further suggest that participants began to view English less as a classroom subject and more as a practical lingua franca for academic and professional interaction. Challenges related to varied English proficiency levels and limited opportunities for sustained collaboration were also identified. Overall, this study suggests that a well-structured international visiting lecture can serve as a pedagogically meaningful learning experience that supports competency-oriented English instruction and contributes to internationalization at home practices in non-Anglophone higher education contexts, while acknowledging the contextual and descriptive scope of the case study.